2021
DOI: 10.1021/acs.jpcb.0c11564
|View full text |Cite
|
Sign up to set email alerts
|

Using Deposition Rate and Substrate Temperature to Manipulate Liquid Crystal-Like Order in a Vapor-Deposited Hexagonal Columnar Glass

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
(130 reference statements)
4
20
0
Order By: Relevance
“…In addition to the q 1 peak, weaker peaks are seen at 0.71 and 0.82 Å −1 , corresponding to higher-order diffractions of hexagonally packed columns at 3 q 1 and 2q 1 , respectively. 22,23 The weak higher-order diffractions indicate a nearly sinusoidal intercolumn density modulation. In addition to columnar order, Kelber et al have observed the π stacking order in this system, giving rise to a scattering peak at 1.8 Å −1 and corresponding to a real-space distance of 3.5 Å.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the q 1 peak, weaker peaks are seen at 0.71 and 0.82 Å −1 , corresponding to higher-order diffractions of hexagonally packed columns at 3 q 1 and 2q 1 , respectively. 22,23 The weak higher-order diffractions indicate a nearly sinusoidal intercolumn density modulation. In addition to columnar order, Kelber et al have observed the π stacking order in this system, giving rise to a scattering peak at 1.8 Å −1 and corresponding to a real-space distance of 3.5 Å.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22 Bishop et al studied the glasses of PNP prepared by PVD and found that the columnar order in thin films can be systematically tuned by the deposition temperature and deposition rate. 23 The system offers a large temperature window between T Col/I and the glass transition temperature to allow the development of columnar order, a useful feature for testing our hypothesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, the rate of material deposition affects the structural anisotropy, thermal stability, and density of the vapor-deposited glass. 22 , 27 , 28 Likewise, the temperature of the substrate ( T sub ) during deposition can modify the surface equilibration kinetics, stability, molecular orientation, and many others. 11 , 16 , 29 35 Focusing on the deposition rate, especially around 0.5 nm s –1 , the molecules are said to obtain enough time for the configurational sampling, allowing high density and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Figure a,b illustrates the 2D-GIWAXS results of an AnB4Ph neat thin film and the calculated order parameter ( S GIWAXS ) of 0.61 for a ππ stacking along the normal direction to the substrate. Here, when S GIWAXS = + 1, the molecules line up on the substrate horizontally; an order parameter of S GIWAXS = −0.5 corresponds to vertically oriented molecules. , A 0.61 for AnB4Ph neat films is one of the highest reported S GIWAXS for materials applied in OLEDs, considering most of them have S GIWAXS values less than 0.3. ,, Such a S GIWAXS implies that molecules of AnB4Ph are predominately aligned horizontally on the substrate. In addition, the results of 2D-GIWAXS show that the d -spacing of AnB4Ph ππ stacking is around 5.1 Å, which matches reasonably well with the results of the single-crystal X-ray structure of AnB4Ph (Figure c), that is, 4.95 Å between the mean plane comprising molecular array.…”
Section: Resultsmentioning
confidence: 97%